Royal Challengers Bangalore : pricing of tickets at the stadium - Sahay, Arvind; Tiwari, Tara (London : Indian Institute of Management, Ahmedabad, 2019)
Royal Challengers Bangalore, an IPL franchise cricket team, represented Bangalore city in the Indian Premier League (IPL). The team had a huge fan following and a brand valuation of USD 88 million in 2017. RCB made profits worth INR 3.15 crore for the first time in FY17.At the beginning of the season of 2018, the team was looking to come up with an approach to price the tickets to all sets of audiences at the stadium to overcome the losses incurred in the past, and gain profits in the future.
Originally Published InSahay, A., & Tiwari, T. (2019). Royal Challengers Bangalore: Pricing of Tickets at the Stadium. IIMA/MAR0498. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cricket teams -- India -- Bangalore -- Case studies; Cricket -- Economic aspects -- India -- Bangalore -- Case studies